When "negative" behaviors are positive a contextual analysis of the long-term effects of problem-solving behaviors on changes in relationship satisfaction.[article]. - McNulty, James K.
How should partners discuss the problem that arise over the course of their intimate relationships? Prior studies have provided inconsistent answers to this question, with some suggesting that partners benefit avoiding negative behaviors and others suggesting that partners benefit by engaging in negative behaviors. The 2 longitudinal studies of newly weds described here reconcile these inconsistent findings by r
Keywords: Communication; Negative behavior; Context; Marriage; Problem-solving.